A high resolution shapefile of the Andean biogeographical region - Romano, Gonzalo Matías (2017)
Biogeographical analyses have proven to be an efficient complement to classic ecology. An ecoregional layer based on Morrone understanding of the Andean region and its sub-regions was constructed. This high-resolution layer was generated with GIS software, and it enables to include ecoregions as categorical variables into species distribution modelling software.